Surgical management of intrahepatic and hilar cholangiocarcinoma: liver resection versus liver transplantation - Nirhali, Ria P.; Bhoir, Reshma M.; Prajapati, Ram P.; Chaudhary, Ashish Y.; Uikey, Rahul H. (International Surgery Journal, 2023)
The incidence of cholangiocarcinoma is increasing worldwide. Patients present with abdominal pain, whereas weight loss and malaise are symptoms of advanced disease. Jaundice occurs when there is hilar obstruction by the tumor. Surgical management involves resection of the affected hepatic segments or liver transplantation, which requires a dedicated multidisciplinary team approach, and promising outcomes are seen in high-volume centres. The authors employed a search strategy for databases like PubMed and Google Scholar. The authors then reviewed the articles using the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines and compared data concerning postoperative complications, recurrence rates, five-year survival rates and prognosis. Liver resection confers long-term survival in patients with intrahepatic cholangiocarcinoma, though the prognosis and morbidity of this procedure are still gloomy. Liver transplantation could be an option, either in early stages diagnosed in the context of chronic liver diseases or locally advanced tumors, when neoadjuvant treatments have achieved sustained tumor response without extrahepatic tumor spread.